Boundary-Layer Processes Producing Mesoscale Water-Vapour Variability over a Mountainous Island - Adler, Bianca (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2014)
Over complex terrain, spatial inhomogeneities of pre-convective atmospheric conditions occur due to convection and mesoscale transport processes. This thesis focuses on the identification of these processes over the mountainous island of Corsica and on the evaluation of their impact on the spatial variability of water vapour, convection-related parameters and the evolution of deep convection by means of observations.